WAWASAN KEBANGSAAN DALAM PUSARAN IMAN KATOLIK (Refleksi Nilai Ajaran Katolik terhadap Keutuhan NKRI Studi di Kota Kupang) - Raudlatul Ulum (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
Catholics in Indonesia perceive that the Republic of Indonesia is founded by many elements of religious entity. The strength of the state completely lies on the agreement of many adherents of religion to unite as an independent country. The spirit of nationalism is the acknowledgement of all people who are equally important to enhance the dignity of Indonesia. The research on Catholics in Kupang is aimed at understanding the relationship of Catholic theology and nationalism in socio-political practices and current realities of the adherents, especially the religious elites, public figures, Catholics in general, and youth. Based on the result of the research, it is highly recommended that the formulation of national identity and guarantee of the religious freedom is important. It is equally important to strengthen the nationalism by enhancing the understanding of Catholic theology.